2000
DOI: 10.1002/1096-9888(200007)35:7<763::aid-jms16>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Some tenets pertaining to electrospray ionization mass spectrometry

Abstract: The field of electrospray ionization mass spectrometry is reviewed with emphasis placed upon advances in the elucidation of fundamental mechanistic aspects of the ionization process that have been reported over the past 10 years. The analytical consequences of these findings are also examined. Eight central conclusions or 'tenets' are presented, as deduced from the body of work contained in 80 references.where r c is the capillary outer radius, V c is the applied electric potential and d is the distance from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
226
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(235 citation statements)
references
References 40 publications
(49 reference statements)
6
226
0
3
Order By: Relevance
“…Those compounds are observed in SPE-extracted DOM and not in dialysis-extracted DOM, with 0.4<O/C<0. 8 9 . Similar results were obtained for Bog 1 DOM.…”
Section: Ft-icr-ms Of Bog 1 and Sos Dommentioning
confidence: 99%
See 1 more Smart Citation
“…Those compounds are observed in SPE-extracted DOM and not in dialysis-extracted DOM, with 0.4<O/C<0. 8 9 . Similar results were obtained for Bog 1 DOM.…”
Section: Ft-icr-ms Of Bog 1 and Sos Dommentioning
confidence: 99%
“…ESI creates positively or negatively charged ions over a wide mass range (10<m/z <3,000) and can be easily coupled with ultrahigh-resolution mass spectrometry [8]. ESI preferentially ionizes polar compounds with functional groups such as amines (-NH 2 ) and carboxylic acids (-COOH) to produce largely intact gaseous ions at room temperature and atmospheric pressure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been proposed that individual ionized sample molecules remain after continuous solvent evaporation and droplet fragmentation (charge-residue model). 21,[28][29][30][31] As shown in Figure 2, a solution of analyte(s) and the solvent are introduced into a needle (∼100 µm in internal diameter) which is charged with the application of an electrical voltage (4-5 kV). The voltage polarity of the needle is positive or negative for positive ion or negative ion generation, respectively.…”
Section: Electrospray Ionizationmentioning
confidence: 99%
“…The droplets continue to shrink and undergo coulombic fission at or close to the Rayleigh limit due to electrohydrodynamic instability. 28 The characteristic feature of ESI that distinguishes it from other ionization techniques is that it generally imparts multiple charges to larger analyte molecules and the extent of multiple charging increases in near proportion with MW. The resulting, highly charged molecular ions are thus within the m/z range where most conventional mass spectrometers function quite well.…”
Section: Electrospray Ionizationmentioning
confidence: 99%
“…However the latter, which is the mechanism of gas phase ion formation from a very small highly charged droplet, is still under investigation and the exact process is not known. According to the literature, there were several experimental evidences that triggered discussion and new hypotheses over this issue [14][15][16]. It was shown that the gas phase ion formation is achieved in three stages: (a) production of charged droplets [17][18][19], (b) Coulomb explosion and disintegration of charged droplets [20][21][22] and (c) formation of gas-phase analyte ions from charged droplets.…”
mentioning
confidence: 99%